Asset Recovery In Corruption Cases In Indonesia: A Human Rights Perspective - Rihantoro Bayuaji; Fikri Hadi (Fiat Justisia: Jurnal Ilmu Hukum, 2025)
The proposal to pardon corruption offenders within a restorative justice framework, as articulated by President Prabowo Subianto, has sparked diverse responses. However, the President later clarified that his statement was not an endorsement of pardoning corrupt individuals but rather an emphasis on the importance of asset recovery in combating corruption. Given that imprisonment has proven ineffective as a deterrent and insufficient in addressing state losses, asset recovery presents a viable legal strategy in corruption law enforcement. This research examines two key issues: the extent to which asset recovery serves as a deterrent in criminal law and its impact on the fulfillment of human rights. Employing a normative juridical approach through statutory and conceptual analysis, the findings suggest that asset recovery not only deters corruption and restores state finances but also advances justice and human rights. Accordingly, this research recommends that the Indonesian House of Representatives and the government expedite the enactment of the Asset Forfeiture Bill (RUU) to strengthen asset recovery mechanisms in corruption cases.